Methane-mediated vapor transport growth of monolayer WSe2 crystals - Jang, Hyeon Sik; Lim, Jae Young; Kang, Seog Gyun; Hyun, Sang Hwa; Sandhu, Sana; Son, Seok Kyun; Lee, Jae Hyun; Whang, Dongmok (Nanomaterials, 2019)
The electrical and optical properties of semiconducting transition metal dichalcogenides (TMDs) can be tuned by controlling their composition and the number of layers they have. Among various TMDs, the monolayer WSe2 has a direct bandgap of 1.65 eV and exhibits p-type or bipolar behavior, depending on the type of contact metal. Despite these promising properties, a lack of efficient large-area production methods for high-quality, uniform WSe2 hinders its practical device applications. Various methods have been investigated for the synthesis of large-area monolayer WSe2, but the difficulty of precisely controlling solid-state TMD precursors (WO3, MoO3, Se, and S powders) is a major obstacle to the synthesis of uniform TMD layers. In this work, we outline our success in growing large-area, high-quality, monolayered WSe2 by utilizing methane (CH4 ) gas with precisely controlled pressure as a promoter. When compared to the catalytic growth of monolayered WSe2 without a gas-phase promoter, the catalytic growth of the monolayered WSe2 with a CH4 promoter reduced the nucleation density to 1/1000 and increased the grain size of monolayer WSe2 up to 100 µm. The significant improvement in the optical properties of the resulting WSe2 indicates that CH4 is a suitable candidate as a promoter for the synthesis of TMD materials, because it allows accurate gas control.
Keywords: 2D material; Methane promoter; Monolayer; Single-crystal; TMD; WSe2